Similarities and differences in intrapopulation trait correlations of co‐occurring tree species: consistent water‐use relationships amid widely different correlation patterns. Issue 9 (14th September 2018) - Messier, Julie; Violle, Cyrille; Enquist, Brian J.; Lechowicz, Martin J.; McGill, Brian J.
Abstract : Premise of the Study: General relationships among functional traits have been identified across species, but the forces shaping these relationships remain largely unknown. Adopting an approach from evolutionary biology, we studied similarities and differences in intrapopulation trait correlations among locally co‐occurring tree species to assess the roles of constraints, phylogeny, and the environmental niche in shaping multivariate phenotypes. We tested the hypotheses (1) that intrapopulation correlations among functional traits are largely shaped by fundamental trade‐offs or constraints and (2) that differences among species reflect adaptation to their environmental niches. Methods: We compared pairwise correlations and correlation matrices of 17 key functional traits within and among temperate tree species. These traits describe three well‐established trade‐off dimensions characterizing interspecific relationships among physiological functions: resource acquisition and conservation; sap transport and mechanical support; and branch architecture. Key Results: Six trait pairs are consistently correlated within populations. Of these, only one involves dimensionally independent traits: LMA‐δ 13 C. For all other traits, intrapopulation functional trait correlations are weak, are species‐specific, and differ from interspecific correlations. Species intrapopulation correlation matrices are related to neither phylogeny nor environmental niche. Conclusions: The results (1) suggest that the functional design of these species is centered on efficient water use, (2) highlight flexibility in plant functional design across species, and (3) suggest that intrapopulation, local interspecific, and global interspecific correlations are shaped by processes acting at each of these scales.